A dangerous idea : the Scopes trial, the original fight over science in schools - Levy, Debbie (Bloomsbury Children's Books, 2025)
"In 1925, when Tennesse lawmakers banned the teaching of evolution in public schools, teacher John Scopes challenged the law--and set off a gripping circus of a legal battle. Two masterminds faced off in court in a blistering debate over creationism and natural selection. A narrative nonfiction book on the Scopes Monkey Trial"--